Determination of residual stresses using X-ray powder diffraction with nonlinearity in d vs. sin2ψ in case of texture or stress gradient - Qin, Ling (My University, 2009)
Mechanical and corrosion properties of metallic materials, such as fatigue and stress corrosion resistance, sometimes depend on the residual stress. X-ray diffraction can be used to measure the residual stresses in polycrystalline materials. Normally, the classic d-sin2-method is used to derive the stress from the diffraction data. However, there could be a strong influence of crystallographic texture or stress gradient on the results of X-ray diffraction residual stress measurement. In the case of X-ray diffraction, very limited penetration depth of X-ray beams confine the stress measurement to a free surface for where the stress is usually assumed to be biaxial, namely the stress components, 3j, normal to the surface are zero. The d-sin2-curves are generally linear. When texture is present oscillation of the d-sin2-curves occurs. In order to circumvent this, different {hkl} reflections were employed for the X-ray powder diffraction stress measurement. On the other hand if the condition deviates from the biaxial case, namely the stress gradient exists, a curved d-sin2 may appear. The grazing incident X-ray diffraction was used to avoid the stress gradient. In the present investigation using the {200} for residual stress measurements instead of the {211} resulted in linear d vs. sin2 in ferrite for the studied samples. In one studied sample, a curved d vs. sin2 plot was caused by the large stress gradient. However, when grazing incident X-ray diffraction was used, a linear d-sin2was obtained. High index reflection such as {651+732} with Mo radiation could be beneficial to eliminate the effect of texture. However, because of low intensities, it is therefore very time consuming and not recommended in normal practice. The heat treatments up to 250°C do neither change the texture structure in 11R51 samples nor the residual stress state in the studied 11R51 samples. Further work for the so-called crystallite group method is suggested in order to try numerically to fit the oscillatory d vs. sin2 curves with {211} reflection.
Keywords: Materialvetenskap; Konstruktionsmaterial; Materials Science; Construction materials